Seabed Morphological Prediction with Application to Mobility and Burial of Munitions - Pessanha, Vinicius Santos (2022)
Hundreds of sites in littoral and inland waters across the United States have been reported as possibly containing underwater munitions, a safety hazard for the general public. Therefore, it is critical to determine and predict munition location and depth to implement remediation strategies. The mobility of munitions may be influenced by currents, waves, and seafloor slope. Burial depth may be affected by scour, sediment accretion, wave-induced liquefaction, and bedform migration. Here, environmental conditions and morphological evolution are investigated by examining observational data and modeling analyses to better understand the physical processes influencing the burial and mobility of munitions. The environmental models (Delft3D) are validated using observations from field experiments. A coupled Delft3D-object model capable of predicting the mobility and burial of objects on a sandy seafloor is presented. Although the object model limitation considers only cylindrical objects on flat seafloor, ignoring pitch and yaw movements, the coupled Delft3D-object model predictions agree well with observations. In addition, processes such as sediment transport, wave-induced liquefaction, and sand wave migration are examined. The findings show that environmental conditions from Delft3D can be used as a forcing term by other models (e.g., object and wave-induced liquefaction models), which is a valuable tool for predicting the fate of munitions.